Respuesta :
If you would like to solve the equation 2 * x^2 + 8 * x = x^2 - 16, you can calculate this using the following steps:
2 * x^2 + 8 * x = x^2 - 16
2 * x^2 - x^2 + 8 * x + 16 = 0
x^2 + 8 * x + 16 = 0
(x + 4) * (x + 4) = 0
x = - 4
The correct result would be x = - 4.
2 * x^2 + 8 * x = x^2 - 16
2 * x^2 - x^2 + 8 * x + 16 = 0
x^2 + 8 * x + 16 = 0
(x + 4) * (x + 4) = 0
x = - 4
The correct result would be x = - 4.
Answer:
x = -4 is the only solution.
Step-by-step explanation:
The given equation is 2x² + 8x = x² - 16
We can find the value of x by solving the equation.
(2x² + 8x) - x² = (x² - 16) - x²
x² + 8x = - 16
(x² + 8x) + 16 = (-16) + 16
x² + 8x + 16 = 0
(x + 4)² = 0 [ Since a² + b² + 2ab = (a + b)²]
⇒ (x + 4) = 0
x = -4
Therefore, x = -4 is the only solution of the given equation.